Lie group and RK4 for solving nonlinear first order ODEs - Altoum, Sami H. (International Journal of Applied Mathematical Research, 2016)
This paper deals with a numerical comparison between Lie group method and RK4 for solving an nonlinear ordinary differential equation. The Lie group method will be introduced as a analytical method and then compared to RK4 as a numerical method. Some examples will be considered and the global error we be computed numerically.